2018
DOI: 10.1111/ijd.13939
|View full text |Cite
|
Sign up to set email alerts
|

Dermatology hospitalists: a multicenter survey study characterizing the infrastructure of consultative dermatology in select American hospitals

Abstract: The results suggest that hospital dermatologists in the U.S. consider inpatient care their niche and devote a majority of their time staffing consults over clinic. The diverse composition of inpatient teams and the number of academic duties held by these physicians suggests they play an important role in medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
(55 reference statements)
0
24
0
Order By: Relevance
“…Surveys in the United States indicate that few dermatologists (14%) spend more than 1 hour in the hospital per week. 13 A recent study of dermatology in Ontario revealed a decrease in the number of dermatologists 17 Community dermatologists operating on fee-for-service model and managing operational costs of a business face greater challenges providing hospital consultations that are more time consuming and poorly remunerated. Another important factor contributing to limited in patient dermatology coverage is a shortage of board-certified dermatologists in Canada and an unbalanced geographic distribution of dermatologists.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys in the United States indicate that few dermatologists (14%) spend more than 1 hour in the hospital per week. 13 A recent study of dermatology in Ontario revealed a decrease in the number of dermatologists 17 Community dermatologists operating on fee-for-service model and managing operational costs of a business face greater challenges providing hospital consultations that are more time consuming and poorly remunerated. Another important factor contributing to limited in patient dermatology coverage is a shortage of board-certified dermatologists in Canada and an unbalanced geographic distribution of dermatologists.…”
Section: Discussionmentioning
confidence: 99%
“…7 Furthermore, dermatology may also contribute with educational support to non-dermatology residents and other healthcare professionals. 7,34 Hu et al 14 argue that dermatologists could also contribute to nurse education about wounds and bandages.…”
Section: Dermatology Contributions In Hospitals and Its Challengesmentioning
confidence: 99%
“…Regarding medical education in dermatology, general practitioners and non-dermatology specialists frequently struggle to properly diagnose and treat skin diseases, which leads to inaccurate diagnoses and inappropriate therapies, as well as references with poor descriptions of skin lesions. 7,14,34,35 This difficulty may be related to the variability in the Dermatology curriculum amongst medical schools, which in some cases may not offer suitable curriculum time to this specialty. 1,35 For this reason, Beshay et al 36 stress the importance of structuring hospital dermatology services and referral and counter-referral processes as stimulators of dermatology education.…”
Section: Dermatology Contributions In Hospitals and Its Challengesmentioning
confidence: 99%
“…1,4 Inpatient dermatology consultations emerged and continue to have profound effects on hospitalized patients regardless of their reason for admission. [1][2][3][4][5][6][7][8][9][10][11] Inpatient dermatologists supply knowledge in areas primary medical teams lack, and there is evidence that dermatology consultations improve the quality of care while decreasing cost. 2,[5][6][7] Establishing correct diagnoses, preventing exposure to unnecessary medications, and reducing hospitalization duration and readmission rates are a few ways dermatology consultations positively impact hospitalized patients.…”
mentioning
confidence: 99%